Deposition behavior regulated by an SPSF@PMIA nanofiber separator for high-performance zinc ion batteries. Issue 46 (15th November 2022) - Hu, Wei; Ju, Jingge; Zhang, Yixuan; Tan, Wei; Deng, Nanping; Liu, Weicui; Kang, Weimin; Cheng, Bowen
Abstract : The non-uniform ion deposition of zinc anodes forming zinc dendrites and the side reactions hinder the large-scale application of zinc ion batteries (ZIBs). Abstract : The non-uniform ion deposition of zinc anodes forming zinc dendrites and the side reactions hinder the large-scale application of zinc ion batteries (ZIBs). Herein, a functional SPSF@PMIA (SP) separator is reported to achieve a dendrite-free and stable zinc anode by regulating the uniform deposition of zinc ions. The SP separator with micro–nano-sized porosity provides more ion paths and facilitates the deposition of zinc ions. At the same time, the –SO3 − in repelling anions and the negatively charged –CO–NH– are susceptible to electrostatic attraction with zinc ions, which allows the selective passage of zinc ions and directs its orderly deposition on the zinc anode surface. As a result, zinc anodes equipped with SP separators showed extremely long cycle life (over 1000 h), low voltage hysteresis (58 mV at 1 mA cm −2 ) and high coulombic efficiency (97.8%). In addition, the SP separator reduces the nucleation overpotential of zinc ions, which greatly alleviates anodic corrosion and promotes homogeneous nucleation of zinc ions. More importantly, the SP separator has excellent ionic conductivity and wide applicability, which can be configured with different electrolytes and different combinations of cathode materials, and shows outstanding reversibility over thousands of cycles. This work shows that the use of separators to regulate ion deposition is an effective strategy to achieve dendritic free zinc anodes and provides a new perspective for research into developing long-life, high-stability, and low-cost separators for ZIBs.